Identification of Managerial Competency Knowledge of Management Students at Jenderal Achmad Yani University - Aam Rachmat Mulyana; Khaerul Rizal Abdurahman (Journal of Business and Management Review, 2021)
The development of increasingly sophisticated technology is driving the era of industrial revolution 4.0, impacting Indonesian millennials entering the era of the digital economy, artificial intelligence, big data, robotics, and so on, or known as disruptive innovation phenomenon. The development of entry-level managers shows that in 2011, the company's demand was smaller than the availability of first-level managers. While it is estimated that in 2020, the company's demand will be greater than the availability of first-tier managers. This causes Indonesia to experience a gap between the needs and availability of managers both in quality and quantity of 40 to 60 percent. This study emphasized on the identification of general managerial competency knowledge, competencies seen from the frequency of managerial competency knowledge use Managerial competency identification is carried out using semi-open questionnaires, in the form of assessment of 14 manager competencies contained in generic competency model of managers from Spencer & Spencer (1993) as a reference list of competency assessment. This study used a sample of some students who were in the 7th semester as many as 192 students. The results of this study showed the highest order of Knowledge Managerial Competency occupied by Analytical Thinking (Impact and Influence) while the lowest order occupied by Developing Other (Developing others), as well as low knowledge of competency impact influence, initiative, and information seeking in students of study programs majoring in management.